Overview of Characteristics of Parathyroid Tumor Patients at Dr. Hasan Sadikin General Hospital Bandung, Indonesia: A 5-Year Study - Tobing, Richard SHL; Kiki A Rizki; Monty P Soemitro; Maman Abdurahman; Yohana Azhar; Dodi Hartoni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Parathyroid tumors are the most common endocrine neoplasms, with hyperparathyroidism as the main clinical manifestation. Parathyroid adenoma is the most common benign neoplasm, while parathyroid carcinoma is relatively rare but difficult to differentiate from benign disorders. This study aims to describe the characteristics of parathyroid tumor patients at Dr. Hasan Sadikin General Hospital (RSHS) Bandung over the last 5 years. Methods: This descriptive observational research was carried out by collecting medical record data from parathyroid tumor patients at RSHS Bandung for the 2019-2023 period. Parameters identified included age, gender, and histopathological type. Data analysis was carried out using SPSS univariately. Results: There were 12 patients with parathyroid tumors with an increasing trend in cases over the last 5 years. The average age of patients was 37.33 years, with the majority (9 cases) being women. Parathyroid adenoma was the most common histopathological type (8 cases), followed by parathyroid carcinoma (2 cases), osteitis fibrocystica (1 case), and bone deformity (1 case). One patient with parathyroid adenoma was also diagnosed with fibrous dysplasia. Conclusion: The majority of cases of parathyroid tumors at RSHS Bandung occur in women, with the incidence of parathyroid carcinoma being the same in men and women. Parathyroid adenoma is the most common histopathological type, and bone abnormalities complications can occur in patients with parathyroid disorders (3 patients).